Investigating storage‐discharge relations in a lowland catchment using hydrograph fitting, recession analysis, and soil moisture data. Issue 7 (29th July 2013) - Brauer, C. C.; Teuling, A. J.; Torfs, P. J. J. F.; Uijlenhoet, R.
<x xml:space="preserve">Abstract</x> [1] The relation between storage and discharge is an essential characteristic of many rainfall‐runoff models. The simple dynamical systems approach, in which a rainfall‐runoff model is constructed from a single storage‐discharge relation, has been successfully applied to humid catchments. Here we investigate (1) if and when the less humid lowland Hupsel Brook catchment also behaves like a simple dynamical system by hydrograph fitting, and (2) if system parameters can be inferred from streamflow recession rates or more directly from soil moisture storage observations. Only 39% of the fitted monthly hydrographs yielded Nash‐Sutcliffe efficiencies above 0.5, from which we can conclude that the Hupsel Brook catchment does not always behave like a simple dynamical system. Model results were especially poor in summer, when evapotranspiration is high and the thick unsaturated zone attenuates the rainfall input. Using soil moisture data to obtain system parameters is not trivial, mainly because there is a discrepancy between local and catchment storage. Parameters obtained with direct storage‐discharge fitting led to a strong underestimation of the response of runoff to rainfall, while recession analysis leads to an overestimation.